Incidence and Control of Poplar Stem Borer, Apriona cinerea, Chevrolet (Cerambycidae : Coleoptera) in Paonta Valley of Himachal Pradesh - Singh, Rajpal; Verma, T. D. (Indian Forester, 1998)
Incidence of Poplar stem borer, Apriona cinerea, Chevrolet on plants of 4 age groups viz. 6 months, 1-2,2-3 and 5-6 years was recorded at village Jagatpur, Paonta Valley, Sirmour, Himachal Pradesh during 1994. No attack of the pest was recorded on 6 months old plants but 2-3 year aged plants were heavily infested (88%) by the pest as compared to other age groups where infestation ranged between 2-27%. Maximum mean number of holes bored per plant in the most susceptible age groups was 7.6 and 23.0 respectively. Out of the five insecticides viz. methyl parathion, dichlorvos, cypermethrin, phorate and furadan and thrce modes of insecticidal application spot treatment, spraying and soil treatment were tested against this borer in summer of 1994. Spot and spray applications of methyl parathion, dichlorvos and cypermethrin each at 0.01 % conc. were found to give 7.80 per cent kill of the pest. Soil application of phorate and furadan @ 25 gm/plant was found ineffective.